Exploratory Data Analysis (EDA) of Marriage Patterns in Kabupaten Banjar Using Machine Learning Approaches - Mambang; Subhan Panji Cipta; Muhammad Zulfadhilah; Husna Karima (INSTALL: Information System and Technology Journal, 2024)
Marriage is a sacred moment that has a significant impact on the social, economic and demographic structure of a region. This research aims to implement a marriage dataset in Banjar Regency and find a correlation between the number of marriages, education level and age of the bride and groom using Exploratory Data Analysis (EDA) techniques and machine learning approaches. The method used is a quantitative method with observation and analysis using EDA and machine learning. The research results show that there is a strong correlation between the number of marriages and the age of the bride and groom (r = 0.99) and between the number of marriages and the education level of the bride and groom (r = 0.99). In addition, a perfect correlation was found between the ages of the groom and the bride (r= 0.99) as well as between the educational levels of the groom and the bride (r = 1). This analysis provides a better understanding of marriage patterns in Banjar Regency and shows that couples aged 21-30 years have a high positive correlation with the number of marriages. It is hoped that these results can become the basis for social policies and educational programs related to marriage.